Strategic treatment approach to common reproductive problems in livestock - Kumar, Abhishek; Bisla, Amarjeet; Rautela, Rupali; Ngou, Athanas Alex; Kumar, Brijesh (Indian Farming, 2020)
Indian dairy is an epitome of rural industry where marginal, small and medium dairy producers contribute to the national milk pail that is collected, pasteurized, pocketed and marketed by a multitude of government, cooperatives, private chilling and processing centres. Under these production settings, it is difficult to ascertain the prevalence of infertility with its causes in the cow due to lack of records and deregulated movement of animals among the clients. Here, an attempt has been made to compile the strategic treatment approach for anoestrus, repeat breeding, metritis complex (RFM, metritis, endometritis and pyometra complex) and cystic ovarian disease (COD) which have major impact on economy of the farmers through antagonizing fertility of dairy animals.